Estudio de prefactibilidad para la instalación de una cafetería temática de cereales con lácteos de colores - Amans Paredes, Andrea Gabriela (2020)
This pre-feasibility study aims to demonstrate the feasibility of implementing a themed cereal cafeteria with colored dairy products. It consists on a bowl of cereal, dairy (which you can color up) and the possibility of adding toppings. Primary sources were used: surveys of 1) Parents who take their children to the cafeteria 2) Young people between 13 and 25 years old. A demand for the first year of 10 477 bowls per month was estimated. It was projected for the next 7 years using as a criterion for its expansion, the annual population growth. As for the location, it was considered from the beginning to place it somewhere that is already busy. Using the so called “ranking of factors”, finally the place chosen was Jockey Plaza Shopping Center. To find the service dimension, the following factors were evaluated: the market, the availability of raw material, investment, technology and the breakeven point. This last one was determined as the minimum limit: 91 daily dishes whereas the maximum is the market: 349 daily dishes. Project engineering contemplates: the service’s flow, technology required and capacity. Also, the program of operations is elaborated as well as the schedule and the physical distribution of the cafeteria (90 square meters). The administrative organization of the cafeteria: 10 operators (working in shifts so there’s always 5 operators at the place). Also, a local administrator and his assistant. Chapter seven focuses on project flows and evaluation: investments, working capital, income budget, production cost table, sales expenses, debt payment table, depreciation and amortization. Obtaining a financial NPV of S/483 855, a financial IRR of 340% and a cost benefit ratio of 12.47. For the social evaluation of the project, indicators are aggregate value, capital density and intensity. To conclude, recommendations, conclusions, bibliography, references and annexes are shown